The rise of the cult of Rembrandt reinventing an old master in nineteenth-century France - McQueen, Alison 1969- (Amsterdam University Press, 2003)
Rembrandt's life and art had an almost mythic resonance in nineteenth-century France with artists, critics, and collectors alike using his artistic persona both as a benchmark and as justification for their own goals. This first in-depth study of the traditional critical reception of Rembrandt reveals the preoccupation with his perceived authenticity
Title from publisher's bibliographic system (viewed on 05 Feb 2021)
Keywords: Rembrandt Harmenszoon van Rijn / 1606-1669 / Criticism and interpretation; Rembrandt Harmenszoon van Rijn / 1606-1669 / Influence; Rembrandt -- Harmensz van Rijn -- 1606-1669; Geschichte 1800-1900; Art criticism / France / History / 19th century; Art, French / 19th century; Druckgrafik; Rezeption; Frankreich; Hochschulschrift